Walking Towards Elfland: Fantasy and Utopia in Ursula K. Le Guin's "The Ones Who Walk Away from Omelas". Issue 2 (July 2018) - Mamola, Gabriel
Abstract : In this paper I revisit Ursula K. Le Guin's "Omelas" by situating it between the often-opposed genres of utopia and fantasy. I explore Le Guin's critical writings to show how she has already involved these genres—and "Omelas"—in an artistic dialogue which can be brought to bear fruitfully on the utopian concerns of "Omelas" and the scholarship surrounding it. In doing so, I reverse a common reading of "Omelas" as "anti-utopian" by showing that the utopian elements of the story are in fact heightened when it is read according to the definitions of fantasy that Le Guin develops in her essay "From Elfland to Poughkeepsie" and other nonfiction writings.